Analisis Perilaku Hidup Bersih dan Sehat (PHBS) di PAUD Desa Somolo-Molo Kecamatan Somolo-Molo Kabupaten Nias - Niat Desita Sari Lawolo; Rizki Ramadhani (Institut Nalanda, 2024)
This study aims to analyze clean and healthy living behavior (PHBS) in PAUD Somolo-molo Village. The type of research used is qualitative descriptive. This research was carried out at PAUD Somolo-molo Village which was carried out for 2 months from July to August 2024 to be precise. The subjects of this research include school principals and educators as well as early childhood students of Somolo-molo Village. The object of the research was clean and healthy living behavior (PHBS) in PAUD Somolo-molo Village. The instruments used in this study are observation sheets and observations, interviews and documentation. The data analysis techniques used are data reduction, data presentation and conclusion or verification. The results of the research carried out are Clean and Healthy Living Behavior (PHBS) in PAUD Somolo-molo Village, Somolo-molo District, Nias Regency has implemented part of PHBS, namely washing hands with soap with running water, at mealtime the teacher looks at the provisions brought by the children so that the results are obtained that there are still children who do not consume healthy food and prefer snacks and or other ready-to-eat drinks, urinate (BAK) and defecate (FEC) in the latrine, then dispose of garbage in its place that has been provided in the classroom and outside the classroom.